2015
DOI: 10.1007/s00405-015-3753-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel predictive marker for the recurrence of nasal polyposis following endoscopic sinus surgery

Abstract: We aimed to determine the value of neutrophil-to-lymphocyte (NLR) ratio for prediction of recurrence in patients subjected to endoscopic sinus surgery. Higher neutrophil counts mean more chronic inflammation so the NLR value could show the inflammatory level resulting with higher incidence of recurrence. From January 2011 to March 2013, we performed a retrospective review of the complete blood count samples from 192 patients with chronic sinusitis who underwent endoscopic sinus surgery. The patients were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
1
17
0
2
Order By: Relevance
“…A recent preliminary investigation conducted by our own research group also showed a significant direct association between CRSwNP recurrence rates and serum basophil counts . When the neutrophil‐to‐lymphocyte ratio (NLR) was investigated vis‐a‐vis CRSwNP recurrence after surgery, it was found to be significant higher in patients whose disease recurred than in those remaining disease‐free . Yenigün also found that patients with recurrent polyposis had a significantly higher preoperative eosinophil‐to‐lymphocyte ratio (ELR) than patients remaining recurrence‐free.…”
mentioning
confidence: 88%
“…A recent preliminary investigation conducted by our own research group also showed a significant direct association between CRSwNP recurrence rates and serum basophil counts . When the neutrophil‐to‐lymphocyte ratio (NLR) was investigated vis‐a‐vis CRSwNP recurrence after surgery, it was found to be significant higher in patients whose disease recurred than in those remaining disease‐free . Yenigün also found that patients with recurrent polyposis had a significantly higher preoperative eosinophil‐to‐lymphocyte ratio (ELR) than patients remaining recurrence‐free.…”
mentioning
confidence: 88%
“…14,15 Boztepe et al reported that in patients with chronic sinusitis who underwent endoscopic sinus surgery, the sensitivity was 39.4% and the specificity was 88.9% for PLR. 16 Zhang et al reported a sensitivity of 76.9% and a specificity of 41.6% for NLR in patients with neutrophilic asthma. 17 In addition, several researchers have investigated these parameters as activation criteria for Behcet's disease, obstructive sleep apnoea syndrome (OSAS), chronic obstructive pulmonary disease (COPD), infective endocarditis and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…9,25 Furthermore, there are also studies suggesting that PLR is a predictive marker in nasal polyposis cases. 12 Considering that another topic in ACP etiology is chronic sinusitis and inflammation, there may be changes in the inflammatory blood parameters of these patients. In our study, there was no statistically significant difference between the pediatric ACP cases and the control group in terms of the specified parameters (p > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…11 Moreover, there are also studies suggesting that these parameters may be considered as an indicator for recurrence in cases of nasal polyposis. 12 Furthermore, in cases of obstructive pathology, it is suggested that especially mean platelet volume (MPV) and PLR ratios show an alteration in children and adults, and this is also a risk factor for possible cardiovascular complications. 13,14 Based on these studies, we considered that the hemogram parameters could vary in cases of pediatric ACPs due to the severity of inflammation and nasal obstruction.…”
Section: Introductionmentioning
confidence: 99%